DFT Study of Alkyl-Substituted Morphine Molecules - Vahid Moeini (Journal of Global Pharma Technology, 2017)
In this paper, (5α,6α)-7,8-didehydro- 4,5-epoxy-17-methylmorphinan-3,6-diol (morphine) as well as alkyl-substituted morphines are studied using density functional theory (DFT) at B3LYP/6-311++g(2d,p) level. The calculated Hartree-Fock (H-F) energies ranged as -1018.0049 to -939.3950 kJ mol-1. Among the three studied molecules, C16H16NO3-CH2CH2CH3 system represents the minimum vibrational frequency, H-F energy as well as the minimum highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) energy gap with 49.939×1010 Hz, -1018.0049 kJ mol-1 and 0.11257, respectively. Keywords: DFT, Hartree-Fock, Morphine, HOMO-LUMO.